Why Does the "Rusalka" Have to Die? The Call of the Other in Zinaida Gippius’s "Sacred Blood" - Larson, K. Maya (Amaltea. Revista de Mitocrítica, 2014)
Why Does the "Rusalka" Have to Die?  The Call of the Other in Zinaida Gippius’s "Sacred Blood"